Search for new phenomena in the dijet mass distribution using pp collision data at √s =8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
Dijet events produced in LHC proton-proton collisions at a center-of-mass energy √s=8 TeV are studied with the ATLAS detector using the full 2012 data set, with an integrated luminosity of 20.3 fb-1. Dijet masses up to about 4.5 TeV are probed. No resonancelike features are observed in the dijet mass spectrum. Limits on the cross section times acceptance are set at the 95% credibility level for various hypotheses of new phenomena in terms of mass or energy scale, as appropriate. This analysis excludes excited quarks with a mass below 4.06 TeV, color-octet scalars with a mass below 2.70 TeV, heavy W′ bosons with a mass below 2.45 TeV, chiral W∗ bosons with a mass below 1.75 TeV, and quantum black holes with six extra space-time dimensions with threshold mass below 5.66 TeV.